Perception of social media use by distance learners in Nigeria (2020)
Perceived ease of use (PEOU) and perceived usefulness (PU) of social media by distance learners may affect its acceptance for learning. These constructs were investigated among 341 distance learners in two universities, the University of Ibadan- UI and the National Open University- NOUN in Nigeria using a questionnaire and was analyzed using frequency and percentages. The main purpose and use of social media in UI and NOUN was to share information (100% and 100%) and for group discussion (96.3% and 100%) respectively. WhatsApp was used daily in NOUN (100%) and UI (91.3%). The PEOU by the respondents in NOUN and UI were both high: requiring a lot of mental effort (100%) and promoting distance interactions between learners and lecturers outside the lecture room (96.9%), while PU in NOUN and UI was also high: it decreased travel expenses (100%) and improved academic performance (100%). Therefore, the high perception of social media use (PEOU and PU) by distance learners should be sustained by facilitators through the adoption of social media for all their courses.